Social Integration and Psychological Wellbeing in a Sample of the Swedish-speaking Minority of Western Finland - Ingrida Grigaitytė; Karin Österman; Kaj Björkqvist (Technium Social Sciences Journal, 2020)
The role of social integration in determining subjective psychological wellbeing in a sample of Swedish-speaking Finns in Ostrobothnia was investigated. A questionnaire was completed by 298 respondents (208 females, 90 males). The mean age was 32.7 years (SD 13.4) for females and 28.9 years (SD 13.4) for males. The age span was between 16 and 90 years. The questionnaire consisted of four scales measuring social integration. Females scored significantly higher on access to social benefits, positive social relations, and trust in the Finnish judiciary system. No sex difference was found for satisfaction with the neighbourhood. The mean values were overall high for both females and males. Respondents over 30 years of age reported significantly more positive social relations and more satisfaction with the neighbourhood compared to respondents under the age of 30. Respondents belonging to a group with high scores of social integration scored significantly lower on anxiety, depression, and somatisation. Conclusively, social integration can be regarded as a resource for psychological health.